Pemetaan Status Hara Phospor (P) Tersedia, pH dan C-Organik pada Lahan Kelapa Sawit di Desa Lawonua Kecamatan Besulutu Kabupaten Konawe - Syam, Bambang Sulistio Hadi; Ginting, Sahta; Zulfikar, Zulfikar (CV. Eduartpia Publisher, 2024)
Nutrient status can be used as a basis for determining soil fertility, therefore appropriate land management actions can be planned. This study aims to determine the nutrient status of available P, pH and C-organic soil and appropriate management actions. The research was conducted on oil palm land in Lawonua Village, Besulutu District, Konawe Regency from May to June 2022. Soil surveys were conducted using the free grid method with a semi-detailed survey level at a map scale of 1:10,000 with an observation level of one sample for every 25 ha, where observation points have been systematically confirmed in the form of slope map units. In this study, these special characteristics have been overlaid and made in the form of a slope map. Soil sampling was conducted on each slope, namely flat slope class (0-8%), gentle slope class (8-15%), moderately steep slope class (15-25%), steep slope class (25-45%), and very steep slope class (>45%) which had previously been determined point/location based on land cover and slope. Soil samples were taken around 500 m or every 25 ha representing one sample point to be analyzed in the laboratory for P-availability, pH and soil C-Organic content. The results showed that oil palm land in Lawonua Village, Besulutu Sub-district, Konawe Regency has very high to high P-available content (17.02 -23.11 ppm), acidic to slightly acidic soil pH (4.81-5.12) and low C-organic between 1.44% to 1.87%. Appropriate management actions on oil palm land require efforts to increase phosphorus through fertilization, C-Organic through the use of organic fertilizers, and increase soil pH through liming and applying the principles of good farming practices.